O corpo simplesmente corpo - Silvino Santin (Universidade Federal do Rio Grande do Sul, 2001)
The human "corpority" became a subject that touches a great number of research of different áreas. The biology, especially by the progress of genetics, gives the most relevant facts to feed the discussion. The human science, particularly, the anthropology and sociology are these ones that feed themselves with more intensity ofthose facts. This paper is an invite to reflect about basics questions of the bodily man.